Synthesis and modification of apatite nanoparticles for use in dental and medical applications - Masahiro Okada; Takuya Matsumoto (Elsevier, 2015)
Synthesised hydroxyapatite (HAp) exhibits excellent biocompatibility, making it an ideal candidate for use as a hard tissue substitute material. Nanoscale-size effects and surface phenomena impart HAp nanoparticles with unique properties compared to the conventional-sized HAp ceramics. Modification of HAp is also important for regulating its physiochemical properties. In this review, methods of HAp synthesis and modification, and various applications of HAp nanoparticles for dental and medical treatment are discussed.